Special homogeneous curves - Lindemann, David (MATHEMATICA SCANDINAVICA, 2024)
We classify all special homogeneous curves. A special homogeneous curve H consists of connected components of the hyperbolic points in the level set {h=1} of a homogeneous polynomial h in two real variables of degree at least three, and admits a transitive group action of a subgroup GGL(2) on H that acts via linear coordinate change.